Prince Caspian: the return to Narnia - C. S. LEWIS; C.S. LEWIS (New York C.S. LEWIS, 1994)
the Pevensie children (Georgie Henley, Skandar Keynes, William Moseley, Anna Popplewell) return to the magical land of Narnia and find that 1300 years have passed there.
Keywords: return to Narnia roughly 1,300 years after their initial rule. The narrative focuses on the overthrow of a Telmarine usurper by the rightful heir; the importance of maintaining faith in unseen, higher powers (Aslan) even during dark times, the necessity of courage in the face of insurmountable odds, and the value of humility in leadership